Eating me up inside: Priming attachment security and anxiety, and their effects on snacking. (September 2013) - Wilkinson, Laura L.; Rowe, Angela C.; Heath, Georgina H.
Recent research has shown that attachment anxiety (a model of interpersonal relationships characterised by a fear of abandonment) is a good predictor of disinhibited eating and, in turn, body mass index. However, this association has yet to be explored within an eating episode. The present study investigated the effect of priming attachment security and attachment anxiety on food intake. Normal weight participants ( N = 21) were primed with security and anxiety on separate occasions and given ad libitum access to a snack food. Priming anxiety led to a significantly higher food intake than priming security ( p = .016). We suggest that participants consumed more food in response to the anxious prime in an attempt to manage the resulting feelings of insecurity. These results provide behavioural evidence for a link between attachment anxiety and disinhibited eating.